2017
DOI: 10.1021/acsami.7b06407
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically Cross-linked Elastomer Hybrids with Light-Induced Rapid and Efficient Self-Healing Ability and Reprogrammable Shape Memory Behavior

Abstract: Pristine carbon nanotubes (CNTs) were activated to exhibit Diels-Alder (DA) reactivity in a polymer matrix, which was modified with monomers containing furan groups. The DA-active polymer matrix was transferred into a dynamic reversible cross-linked inorganic-organic network via a Diels-Alder reaction with CNTs, where pristine CNTs were used as dienophile chemicals and furan-modified SBS acted as the macromolecular diene. In this system, the mechanical properties as well as resilience and solvent resistance we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(46 citation statements)
references
References 51 publications
4
42
0
Order By: Relevance
“…Recently, it was reported that the addition of carbon nanotubes, graphene oxide nanosheets, and other nanoparticles into polymer matrix surface activated the reactivity of DA due to their outstanding photothermal effect. [114][115][116] For instance, the carbon nanotubes (CNTs) were embedded into the polymer matrix surface modified by monomers containing furan groups (Figure 11b,c). [116] Under the laser irradiation, the surface cracks can be efficiently healed since the photothermal effect of CNTs activated the DA reaction at interface (Figure 11d).…”
Section: Self-healing Based On Reversible Covalent Bondsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it was reported that the addition of carbon nanotubes, graphene oxide nanosheets, and other nanoparticles into polymer matrix surface activated the reactivity of DA due to their outstanding photothermal effect. [114][115][116] For instance, the carbon nanotubes (CNTs) were embedded into the polymer matrix surface modified by monomers containing furan groups (Figure 11b,c). [116] Under the laser irradiation, the surface cracks can be efficiently healed since the photothermal effect of CNTs activated the DA reaction at interface (Figure 11d).…”
Section: Self-healing Based On Reversible Covalent Bondsmentioning
confidence: 99%
“…[114][115][116] For instance, the carbon nanotubes (CNTs) were embedded into the polymer matrix surface modified by monomers containing furan groups (Figure 11b,c). [116] Under the laser irradiation, the surface cracks can be efficiently healed since the photothermal effect of CNTs activated the DA reaction at interface (Figure 11d). After that, different concentrations of graphene oxide nanosheets enhanced the healing effect of polyurethane as illustrated in the Figure 11e, [115] generated heat under light and further promoted DA reaction at interface as demonstrated in Figure 11f.…”
Section: Self-healing Based On Reversible Covalent Bondsmentioning
confidence: 99%
See 1 more Smart Citation
“…Properties such as self-healing and shape memory, besides the "classical effects" on thermal and mechanical ones, are easily added to the composite behavior. The sensitivity to multiple external stimuli such as electricity, irradiation, and heat [11,18,53,54], represents a focal point for the design of smart materials. An added value in this case is the possibility (via irradiation) of remote-induced self-healing as well as of ultrafast kinetics [55].…”
Section: Future Outlookmentioning
confidence: 99%
“…One of the main driving forces behind the use of such a strategy is the presence of special end properties. For example, the dynamic nature of thermally reversible interactions (as a function of temperature) endows composites with self-healing behavior [11,13,[15][16][17] and shape-memory characteristics [18,19].…”
Section: Introductionmentioning
confidence: 99%